Advanced primary vaginal squamous cell carcinoma: A case report and literature review - Shen, Yue; Meng, Xiangkai; Wang, Lili; Wang, Xiaoxiao; Chang, Hua (Frontiers in Immunology, 2022)
Background: Vaginal cancer is a rare gynecological malignancy, and there are few relevant and specific guidelines for vaginal cancer in our country and abroad. Here, we report the case of a patient with advanced, primary vaginal squamous cell carcinoma who successfully underwent integrated treatment. Case introduction: A 64-year-old Chinese woman underwent subtotal hysterectomy for uterine fibroids in 1998 and laparoscopic extensive residual cervical resection, bilateral ovarian salpingectomy, and pelvic lymph node dissection in the First Affiliated Hospital of China Medical University in 2018 for terminal cervical adenocarcinoma (stage IB1). There was no postoperative review. The patient experienced vaginal discharge in March 2020, and vaginal bleeding occurred in July 2020. Based on a gynecological examination, colposcopy biopsy with histopathological examination, computed tomography scan, and tumor marker levels, the patient was diagnosed with stage I VA vaginal squamous cell carcinoma. After three phases of treatment (sequential treatment with chemotherapy plus radiotherapy, chemotherapy combined with immunotherapy, and immunotherapy combined with antivascular therapy), her condition improved. Her current state is generally good, and she has achieved complete remission. Conclusion: We report a rare case of a patient with advanced primary vaginal squamous cell carcinoma combined with cervical adenocarcinoma. The patient was treated for approximately 2 years, and immunotherapy combined with antivascular therapy showed good results. We will continue to follow up with the patient and monitor her response to the current treatment process